Formal Analysis of Improved and Secure Architecture of E-voting System using Hierarchical Coloured Petri Nets - Ahmad, Z.; Ahmad, F.; Gondal, Z. A (The Nucleus, 2020)
Casting a vote is the fundamental right of any citizen. Pakistan follows the traditional manual voting system and there are number of factors influencing in such a way that put a question as if the vote has been casted correctly and should be considered towards final count. Manual counting process of vote do not provide the security measures minimizing the attempts of frauds like increase or decrease in the vote count. Therefore, the idea of secure and improved E-voting system is proposed to overcome such flaws in current voting system in Pakistan. In this manuscript, an improved component-based architecture, security features and future recommendations are presented. Different techniques linked with voter’s authentication, confidentiality and integrity are suggested to minimize the flaws and maximize the benefits of voting system. Further, the proposed architecture is formally modelled through ‘coloured Petri nets’ to validate it. Formal analysis is also performed based on the state space generated to simulate the hierarchical coloured Petri net based formal model of proposed E-voting system.